2021
DOI: 10.6023/cjoc202009053
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Strategies Enabling Cross-Dehydrogenative Coupling: Access to C—C Bonds

Abstract: Cross-dehydrogenative coupling (CDC) reactions have been esteemed as one of the straightforward and efficient tool for C-C bond formation. Typically, these reactions are generally realized via solvent-based thermochemistry, using a round bottom flask and a magnetic or mechanical stirrer. With the development of new synthetic strategies, alternative technologies currently available in laboratories that facilitate CDC reactions, such as photochemistry, electrochemistry and mechanochemistry have arisen rapidly, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 146 publications
0
5
0
Order By: Relevance
“…Some elegant works on the construction of C–C, C–O, C–N bonds, etc. have been reported by Ito, 44–50 Bolm, 51–56 Wang, 57–60 Su, 61 Friščić 62–64 and other groups, 65–68 respectively. On the other hand, an electromagnetic mill (EMM) is a novel grinding device and uses small ferromagnetic particles as the grinding media in a rotating electromagnetic field.…”
Section: Introductionmentioning
confidence: 76%
“…Some elegant works on the construction of C–C, C–O, C–N bonds, etc. have been reported by Ito, 44–50 Bolm, 51–56 Wang, 57–60 Su, 61 Friščić 62–64 and other groups, 65–68 respectively. On the other hand, an electromagnetic mill (EMM) is a novel grinding device and uses small ferromagnetic particles as the grinding media in a rotating electromagnetic field.…”
Section: Introductionmentioning
confidence: 76%
“…59 However, the transformation with simple ketones has remained underdeveloped in terms of substrate scopes, stereocontrol, and redox economy. 60 In 2017, we further extended the chiral primary aminocatalysis to a synergistic tricatalytic system for asymmetric CDC involving a photoredox catalyst Ru(bpy) 3 Cl 2 , a hydrogen/electron mediator Co-(dmgH) 2 Cl 2 , and primary aminocatalyst A8 (Scheme 11). 61 The protocol could be applied to various cyclic ketones with substituted tetrahydroisoquinolines under the irradiation of visible light to afford syn-selective adducts with moderate to high diastereo-and enantioselectivity (Scheme 11, 16a−c).…”
Section: Photoredox Catalysismentioning
confidence: 99%
“…Previously, we have shown that chiral primary amine catalysts could work in concert with a photocatalyst for asymmetric α-photoalkylation. , In the past decades, catalytic asymmetric cross-dehydrogenative coupling (CDC) reactions have been explored as powerful methods for constructing C–C bonds between two unmodified C–H bonds . However, the transformation with simple ketones has remained underdeveloped in terms of substrate scopes, stereocontrol, and redox economy . In 2017, we further extended the chiral primary aminocatalysis to a synergistic tricatalytic system for asymmetric CDC involving a photoredox catalyst Ru­(bpy) 3 Cl 2 , a hydrogen/electron mediator Co­(dmgH) 2 Cl 2 , and primary aminocatalyst A8 (Scheme ).…”
Section: Photochemical Synergistic Catalysismentioning
confidence: 99%
“…16 In many of the methods above, visible light or blue LED was applied to provide the necessary energy to overcome the endergonic reactions. 17…”
mentioning
confidence: 99%